Meningkatkan Kemampuan Guru dalam Penggunaan Media Pembelajaran Melalui Teknik Supervisi Kunjungan Kelas pada Pembelajaran Masa Pandemi Covid-19 Guru - Evriza Evriza (Jurnal Syntax Transformation, 2022)
The low quality of human resources, especially educators / teachers, is one of the main problems in the world of education. As the fact that occurred in SMK Negeri 1 Kota Bengkulu, especially the use of media in learning activities in the past year based on the results of the supervision of the principal on 40 teachers found data that in the implementation of teacher learning did not use media. Teachers explain more material when the material can be clarified with media that are easily obtained both available in schools and around schools. Of the 40 teachers in SmK Negeri 1 Kota Bengkulu only 10 people (25%) have used media in learning activities while 30 people (75%) still do not use media. Through this inter-class visit, it is expected that teachers will gain new experiences from their more professional colleagues. School Action Research (PTS) with the subjects of teachers of SmK Negeri 1 Kota Bengkulu amounted to 40 people. In each cycle there are activities of planning, implementation, observation, and reflection. The instrument used is an observation sheet. Observational data is analyzed in descriptive qualitative and descriptive quantitative percentage. The results showed an increase in the ability of teachers in using learning media where in cycle 1 meeting 1 was 60% with sufficient categories, increased at meeting 2 to 67% with good category. In cycle 1I meeting 1 increases to 75% with good categories and there is another increase at meeting 2 to 85% with excellent category. The implementation of supervision with the technique of inter-class visits in cycle I of meeting 1 is 64% with good categories increasing to 76% with good categories at meeting 2, In cycle 2 meeting 1 increases again to 81% with excellent category 2 to 88% with excellent category